Optimizing Natural Resource Products through Sustainable Branding, Human Capital Strengthening, and Financial Resilience in the Age of Millennial and Gen Z Consumers - Rahmantari, Ni Luh Laksmi; Mardika, Agus Putra; Lia Yasmita, I Gusti Ayu; Suryagita Susila Putra, I Putu Dharmawan; Mela Tri Utari, Ni Komang (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This paper explores sustainable branding, human resource capability, and financial sustainability on anesthetic competitiveness of nursery product in Millennial and Gen Z era consumers. Despite young consumers’ strong environmental concern, an attitude–behavior gap is observed between their attitudes and actual purchasing behavior. From interviews with 20 informants including young consumers, producers and fintech developers we conclude that sustainability matters, but only if authenticity and transparency are there to back it up. The challenges for producers are often reduced digital skills, weak financial literacy, and difficult access to capital. These constraints inhibit their ability to market sustainably, generate innovations, and manage financial risks. The research recommends that natural resource enterprises should include sustainable brand credence, robust human resources capability, and better financial resilience in order to thrive and grow in the era of digitalization and environmental awareness in Indonesia.